Peningkatan Aktivitas dan Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti Melalui Metode Kooperatif - Yandriani, Fitri (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
Islamic Religious Education and Moral Character (PAI and BP) play an essential role in shaping students’ character and ethics, as well as enhancing their religious understanding. However, the reality shows that the learning outcomes of PAI and BP at SD Negeri 09 Pauh Lubuk Sikaping still face challenges, particularly in the topic of Asmaul Husna. This issue arises from low student interest, conventional teaching methods, and inadequate learning facilities. This study aims to investigate whether the use of the cooperative learning method, specifically the Team Games Tournament (TGT) model, can improve students’ learning outcomes in the topic of Asmaul Husna. By applying a cooperative approach that involves group discussions and individual tasks, it is hoped that students will become more engaged in the learning process, improving their understanding and learning results. The findings of this study are expected to contribute to the enhancement of PAI and BP teaching quality at SD Negeri 09 Pauh Lubuk Sikaping.